Protection against Cryptococcosis by Using a Murine Gamma Interferon-Producing Cryptococcus neoformans Strain - Wormley, Floyd L. (American Society for Microbiology, 2007)
We evaluated cell-mediated immune (CMI) responses in mice given a pulmonary infection with a Cryptococcus neoformans strain engineered to produce the Th1-type cytokine gamma interferon (IFN-γ). Mice given a pulmonary infection with an IFN-γ-producing C. neoformans strain were able to resolve the primary infection and demonstrated complete (100%) protection against a second pulmonary challenge with a pathogenic C. neoformans strain. Pulmonary cytokine analyses showed that Th1-type/proinflammatory cytokine and chemokine expression were significantly higher and Th2-type cytokine expression was significantly lower in mice infected with the IFN-γ-producing C. neoformans strain compared to wild-type-infected mice. This increased pulmonary Th1-type cytokine expression was also associated with significantly lower pulmonary fungal burden and significantly higher pulmonary leukocyte and T-lymphocyte recruitment in mice infected with the IFN-γ-producing C. neoformans strain compared to wild-type-infected mice. Our results demonstrate that pulmonary infection of mice with a C. neoformans strain expressing IFN-γ results in the stimulation of local Th1-type anti-cryptococcal CMI responses and the development of protective host immunity against future pulmonary cryptococcal infections. The use of fungi engineered to produce host cytokines is a novel method to study immune responses to infection and may be useful in developing vaccine strategies in humans.